Sustainability Strategy for Solar Power Plant: Integrating Sustainable Development and Rural Enviroment - Nurhanifah, Nita Viviani; Rachmawatie, Dessy (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
The development of renewable energy is essential amid the global energy transition, yet the sustainability of solar power plants—both commercial and household—in Bali Province remains low. Access to electricity is a vital component of sustainable development, helping to bridge the gap between rural and urban areas in Indonesia. In 2016, solar power plants were established in Karangasem Regency to electrify rural communities that previously lacked access due to difficult geographical conditions. This study aims to identify and analyze the key factors influencing sustainable solar power growth in Karangasem while offering strategic recommendations. Employing a qualitative approach and the MICMAC method, it explores economic aspects such as job creation, poverty alleviation, and energy investment; social factors like energy access and community participation; environmental considerations including waste management and climate mitigation; and institutional elements involving local regulations and public-private collaboration. The findings highlight that fostering local economic development (ESD), sustainably managing resources (SNRU), and reducing air pollution (AP) are crucial for enhancing environmental quality (EQI) and attracting investment (EI). The study emphasizes the need for collaborative frameworks and robust policy measures to promote renewable energy, ensuring long-term sustainability and advancing rural development and environment in Karangasem Regency, Bali Province.